Qualitative Study of Family Support for Women’s Health Seeking-Behaviour in Rural Areas District Sleman - Jati Untari; Ariyanto Nugroho2 (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2019)
Introduction: Health is a field that is very closely related to women's duties because the role of women is the reproductive role that is in the realm of the household. Health seeking behavior is preceded by a decision-making process that requires social support from spouses or other family members so that it can potentially improve the health status of women and children in the family. This study aims to explore the differences in family support for mothers in health seeking behavior when ANC, childbirth, and toddlers are sick in rural areas. Methods:The study was conducted using qualitative methods with in-depth interviews with 6 mothers, 6 husbands and 4 mother-in-laws who in their families had toddlers who had experienced illness in the last 3 months. The study was conducted in Banaran subvillage, Sleman District. Results :The results found that family support for maternal health seeking behavior during ANC, childbirth and when sick toddlers are always discussed by husband and wife, while the role of in-laws is very small, that is giving advice. In the condition of the childbirth, the family support not only from her husband and mother-in-laws but also from the whole extended family on the part of the mother who does not live in one house. Conclussions: In conclusion, mothers get considerable support from their families, both from their husbands, mother-in-laws or large families who do not live in the same house in health seeking behavior, especially during childbirth.